2011
DOI: 10.1007/s00330-011-2201-8
|View full text |Cite
|
Sign up to set email alerts
|

BI-RADS categorisation of 2708 consecutive nonpalpable breast lesions in patients referred to a dedicated breast care unit

Abstract: This pragmatic study reflects the assessment and management of breast impalpable abnormalities referred for care to a specialized Breast Unit. Multidisciplinary evaluation with BI-RADS classification accurately predicts malignancy, and reflects the quality of management. This assessment should be encouraged in community practice appraisal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
3
8
1
1
Order By: Relevance
“…Supporting this evidence, Hamy et al (30) reported a PPV of 78.7% for non-palpable BI-RADS 5 lesions in their study. One other reason for the lower rate in our study might be the design of this study.…”
Section: Resultssupporting
confidence: 69%
“…Supporting this evidence, Hamy et al (30) reported a PPV of 78.7% for non-palpable BI-RADS 5 lesions in their study. One other reason for the lower rate in our study might be the design of this study.…”
Section: Resultssupporting
confidence: 69%
“…However, the PPV 2 of screening US was only 3.33 % in our study even though there was no statistical significance. One of the most challenging problems for supplemental screening US was a higher rate of BI-RADS category 3 assessments, which are considered as false positive [13,35,41]. In our study, the rate of BI-RADS category 3 of screening mammography was 5.51 % but that of US was 26.6 %, a significantly higher value.…”
Section: Positive Predictive Values Cancer Yields and Bi-rads Categmentioning
confidence: 44%
“…To assess the training performance in breast US, we used BI-RADS descriptors or final assessment whose reliability for the prediction of malignancy has been validated and the interobserver agreement has been found to be good in previous studies (13)(14)(15). In this report, the proportion of correct answers given by radiology residents for margin and echo pattern on breast US was lower than that for the other descriptors (Table 1).…”
Section: Discussioncontrasting
confidence: 40%